Chemical composition and antimicrobial activity of the essential oil from twigs and leaves of Magnolia macclurei (Dandy) Figlar from Ha Giang Province, Vietnam - Thu Ha, Chu Thi; Thai, Tran Huy; Diep, Le Ngoc; Thu Thuy, Dinh Thi; Ky, Nguyen Duc; Tam, Ha Minh (Academia Journal of Biology, 2020)
The chemical composition of the essential oil obtained by hydrodistillation of the twigs and leaves of Magnolia macclurei collected in Hoang Su Phi, Ha Giang Province, Vietnam was analyzed using GC/MS. A total of 38 compounds were detected in essential oil, accounting for 94.49% of the oil, in which 37 compounds were identified accounting for 93.33%. cis-β-Elemene (14,30%), bicyclogermacrene (18,57%), and 10-epi-ᵧ-eudesmol (16,86%) were the main components of essential oil. The minor components present with rather high amount were: Germacrene D (2,12%), guaiol (8,52%), hinesol (2,34%), valerianol (6,76%), and bulnesol (2,93%). Antibiotic activity of the essential oil sample was tested against a Gram positive bacteria Staphylococcus aureus, a Gram negative bacteria Escherichia coli, and a yeast Candida albicans using an agar disk diffusion method. All three microorganisms tested are resistant to the oil from twigs and leaves of M. macclurei. That is exhibited through the inhibitory zone diameters ranging from 4 to 12 mm.